THE EFFECT OF ‘HOT POTATO STRATEGY’ ON THE SECOND YEAR STUDENTS’ ABILITY IN READING COMPREHENSION AT SMPN 18 PEKANBARU - Devi Andriyani; Eliwarti Eliwarti; Supriusman Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This pre-experimental study was conducted by using One-Group Pretest-Posttest design to find out whether or not there is a significant effect of ‘Hot Potato Strategy’ on the second year students’ ability in reading comprehension at SMPN 18 Pekanbaru. The sample of the research was 35 students of class VIII.6 and obtained by using cluster random sampling technique. 40 multiple choices of recount text was the instrument of the test. The students’ scores were analyzed by using Microsoft Excel 2007 and SPSS 23.0 (Statistical Product and Service Solution) for windows. The collected data were analyzed by using t-test formula. The results showed that the mean score of post-test was higher than pre-test (74.14>63.93). Then, it also showed that t-test was higher than t-table (10.048>2.03) at significance level of 5%. Therefore, Alternative Hypothesis (Ha) is accepted and Null hypothesis (Ho) is rejected. It can be concluded that there is a significant effect of ‘Hot Potato Strategy’ on the second year students’ ability in reading comprehension at SMPN 18 Pekanbaru.Keywords: Effect, Hot Potato Strategy, Reading Comprehension